Influencia de los ejercicios de bailoterapia para las madres de familia de la escuela particular mixta “Julio María Matovelle” año lectivo 2012 – 2013 de Puerto Bolívar. - Valiente Cruz, Yuri Vanessa (2015)
At present the human being carries a sedentary life and thus has the need to perform moderate physical activity in particular mothers finding in the bailoterapia energy to improve the health that has served as the basis for creating a new form of physical activity that has taken our society, there is a large influx of people who come to bailoterapia centers, parks, and gyms in which are taught these classes, to get rid of stress, forget about the problems, and improve your figure. This discipline is a mixture of genres of dance combined in choreography adapted to a fitness lounge. It is the combination of music and movement through the dance of different rhythms, stimulating the flow of energy in a harmonious manner and controlled. The music acts as a catalyst for the most varied feelings attenuating the moments of stress, loneliness and anxiety. The bailoterapia is a dialog between the music and the body that favors the emotional stability when raising the production of endorphins, which generate a feeling of pleasure and joy with a direct impact on the levels of self-esteem and motivation.